2021
DOI: 10.1159/000514202
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Lymphocyte Subsets in the Course of COVID-19

Abstract: <b><i>Background:</i></b> Although the pathophysiology of coronavirus disease 2019 (COVID-19) is not clearly defined, among the proposed mechanisms, immune system dysfunction is more likely than others. The aim of this study was to clarify the characteristics and clinical significance of dynamic changes of lymphocyte subsets in the course of COVID-19. <b><i>Methods:</i></b> In this prospective study, the levels of peripheral lymphocyte subsets including CD4<su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
2
33
0
2
Order By: Relevance
“…The early activation phenotype in CD8 is defined by CD38 and HLA-DR expression [ 42 ]. Recently, an increase in the frequency of CD8 + CD38 + HLADR + cells in patients with COVID-19 disease and fatal outcomes has been confirmed [ 43 , 44 ]. In the present work, the severe group presented an increased frequency of CD8 + CD38 + HLADR + cells at admission.…”
Section: Discussionmentioning
confidence: 99%
“…The early activation phenotype in CD8 is defined by CD38 and HLA-DR expression [ 42 ]. Recently, an increase in the frequency of CD8 + CD38 + HLADR + cells in patients with COVID-19 disease and fatal outcomes has been confirmed [ 43 , 44 ]. In the present work, the severe group presented an increased frequency of CD8 + CD38 + HLADR + cells at admission.…”
Section: Discussionmentioning
confidence: 99%
“…A number of hematological abnormalities have been observed in the laboratory features of COVID-19 (7,(10)(11)(12)(13). Several studies concerning changes of lymphocyte subsets and their correlation with the severity and outcome of the disease have been reported in adults (10,14,15). However, there are no studies on lymphocyte subset analyses in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research has shown that lymphocytes and the subsets of CD4+ T cells, CD8+ T cells, B cells, and natural killer (NK) cells also play an important role in the maintenance of immune system function during COVID-19 [ 7 ]. COVID-19 patients exhibit a reduction in the absolute number of lymphocytes, including CD4+ and CD8+ T lymphocytes, which display markers related to activation or exhaustion/senescence, in addition to altered expression of master regulators and several chemokine receptors [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%